Wiara w reinkarnację wśród młodych i dorosłych katolików w Polsce na przełomie XX i XXI wieku. Wyniki badań socjologicznych - Baniak, Józef (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
The article shows faith in reincarnation of some young and adult Catholics in Poland at the turn of the 21st century. The following questions demarcate the research problem: Were some young and adult Catholics in Poland interested in reincarnation at the turn of the twenty-first century and how did they understand its essence and purpose? What percentage of the surveyed young and adult Polish Catholics believed in the ideological assumptions behind reincarnation? Did the surveyed young and adult Polish Catholics use reincarnation as a substitute to their own religious beliefs concerning the fate of the human soul after death and life after death? The basis for answering these questions were the results of sociological research carried out at the turn of the 21st century. The following methods were use in data study: historical-comparative, selection and sampling of research, sociological analysis of the content of research results, statistical analyses and variable correlation assessment. The category of “Young Catholics” was the youth of secondary schools (aged 16–18) and the student youth (aged 19–25), while the category “Adult Catholics” gathered people aged 25–65. The research showed that some young and adult Polish Catholics, who also declare their relationship with the Christian faith and with the Catholic Church, at the same time accepted reincarnation and believed in the journey of the human soul after death, in its diverse incarnations after death. However, they no longer believed in the return of the soul to the same body after the resurrection, as the Catholic Church teaches.